2012
DOI: 10.1007/s11606-012-2079-4
|View full text |Cite
|
Sign up to set email alerts
|

Literacy, Cognitive Function, and Health: Results of the LitCog Study

Abstract: BACKGROUND: Emerging evidence suggests the relationship between health literacy and health outcomes could be explained by cognitive abilities. OBJECTIVE:To investigate to what degree cognitive skills explain associations between health literacy, performance on common health tasks, and functional health status. DESIGN: Two face-to-face, structured interviews spaced a week apart with three health literacy assessments and a comprehensive cognitive battery measuring 'fluid' abilities necessary to learn and apply n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
197
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(212 citation statements)
references
References 47 publications
9
197
5
Order By: Relevance
“…These patterns persisted even after adjusting for demographic covariates including age, sex, and race, as well as clinical covariates such as chronic medical conditions, functional impairment, and cognition. Interestingly, though past evidence has suggested that health literacy may be a proxy for general cognition, 40,41 our results suggest that each has an independent relationship with likelihood of regular Internet use. We found that health literacy was a more important predictor of Internet use for medical or health information than was level of cognitive function, suggesting that interventions specifically targeting health literacy among Internet-using older adults may be effective for narrowing the digital divide by facilitating their ability to obtain medical information online.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…These patterns persisted even after adjusting for demographic covariates including age, sex, and race, as well as clinical covariates such as chronic medical conditions, functional impairment, and cognition. Interestingly, though past evidence has suggested that health literacy may be a proxy for general cognition, 40,41 our results suggest that each has an independent relationship with likelihood of regular Internet use. We found that health literacy was a more important predictor of Internet use for medical or health information than was level of cognitive function, suggesting that interventions specifically targeting health literacy among Internet-using older adults may be effective for narrowing the digital divide by facilitating their ability to obtain medical information online.…”
Section: Discussioncontrasting
confidence: 88%
“…Other covariates were as expected: age greater than 75 years, education less than high school, and low cognitive function were also associated with a lack of regular Internet use. Interestingly, although existing evidence suggests that the relationship between health literacy and other health-related measures in many cases is rendered insignificant by the inclusion of measures of general cognitive function, 40,41 our results remained robust even after adjusting for these. We also repeated the regression analyses entering scores on each of the three cognitive tests separately (rather than in the combined 27-point scale), and our results were unchanged, so we are reporting the results using the combined 27-point scale.…”
Section: Resultscontrasting
confidence: 68%
“…A more complete description of the LitCog study and its battery has been published previously. 13 Northwestern University's Institutional Review Board approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, more recent studies have found that health literacy assessments are strongly correlated with various tests of cognitive abilities, 11,12 such that the relationship between literacy and health outcomes may in part be explained by a more global cognitive skill set. 13 If cognitive and health literacy measures are revealing a similar latent trait, then a clinical screening tool such as the Mini Mental Status Examination (MMSE), 14,15 a brief global assessment of cognitive function, may viably serve as a surrogate measure to identify patients at risk for limited health literacy. The advantages of using the MMSE in this manner could be twofold: 1) it would offer greater face validity of the actual problem, that being limited proficiency for understanding and acting on health information; and 2) the MMSE is already a well-vetted assessment used for clinical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults can have lower health literacy levels because of long-term influences, such as limited education or limited knowledge of expressing themselves [8], yet such limited levels of health literacy can also be, according to the findings of a number of researches that did not include dementia patients, linked to an age-related cognitive decline [9,10,11]. Besides that, several other resources, such as education, word knowledge, and decision-making manner, contribute to health literacy and are connected to recollection or memory function.…”
Section: Pielęgniarstwo XXI Wiekumentioning
confidence: 99%